A STUDY ON DETERMING THE FINANCIAL POSITION BASED ON FINANCIAL DIAGNOSIS IN COMPANIES LISTED ON THE BUCHAREST STOCK EXCHANGE - HADA, Teodor (Annales Universitatis Apulensis Series Oeconomica, 2014)
This study presents aspects related to determining a company’s financial position by means of financial diagnosis, in the case of 64 companies listed on the Bucharest Stock Exchange. The aim of this study is to show, in a wide structure, how to determine a company’s financial position. The study is divided into four paragraphs and their related subparagraphs. In the first paragraph the objective, the research methodology and the novelty brought by this study are revealed. In the second paragraph various viewpoints of financial diagnosis construct are shown, followed by a third paragraph where the variables needed to determine financial position and the rating criteria are established, and in the last paragraph the aggregate score is determined. The end of the study is reserved to establishing conclusions and proposals.